1986
DOI: 10.1016/s0735-1097(86)80330-8
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of global and regional left ventricular function after early thrombolysis in acute myocardial infarction

Abstract: The effect of early myocardial reperfusion (within 4 hours after onset of symptoms) on regional left ventricular function in patients with acute myocardial infarction has been quantitated by analysis of segmental wall motion. Of 533 patients randomized either to conventional coronary care unit therapy or to a reperfusion strategy, in 332 high quality angiograms were obtained 2 to 8 weeks after the onset of myocardial infarction. In those assigned to thrombolytic therapy, angiographic data were also available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 312 publications
(60 citation statements)
references
References 53 publications
3
55
0
2
Order By: Relevance
“…Myocardial necrosis is a process that increases with the elapse of time, with the muscle fibre passing through the stages of dysfunction, stunning and finally death. 13 This was corroborated in our study in which the mean Symptom Needle (S/N) time in the successful group was 3.03 hours as opposed to 7.95 hours in the group, which failed reperfusion. Even in the developed world, the time to admission and the time to treatment in patients admitted with MI is still prolonged, and resources must be allocated to improve these times.…”
supporting
confidence: 80%
“…Myocardial necrosis is a process that increases with the elapse of time, with the muscle fibre passing through the stages of dysfunction, stunning and finally death. 13 This was corroborated in our study in which the mean Symptom Needle (S/N) time in the successful group was 3.03 hours as opposed to 7.95 hours in the group, which failed reperfusion. Even in the developed world, the time to admission and the time to treatment in patients admitted with MI is still prolonged, and resources must be allocated to improve these times.…”
supporting
confidence: 80%
“…[48][49] However, the recovery of this salvaged myocardium is sig nificantly impaired by reocclusion.15*16-50 Two previous clinical studies,15-16 both performed shortly after myocar dial infarction, reported that left ventricular function was significantly better in patients without reocclusion than in those with reocclusion. This difference was largely due to recovery of infarct-zone function in patients without reoc clusion.…”
Section: Left Ventricular Functionmentioning
confidence: 99%
“…2 The subsequent quality of coronary flow appears to be an important prognostic factor. 3 However, angiographic success does not necessarily equate with adequate myocardial perfusion, even after early revascularization.…”
mentioning
confidence: 99%